2021
DOI: 10.14393/rbcv73n2-56597
|View full text |Cite
|
Sign up to set email alerts
|

Monitoramento Fitossanitário Utilizando Sensoriamento Remoto: Avanços e Desafios

Abstract: Problemas fitossanitários, como doenças, pragas e plantas daninhas, que competem com as plantas cultivadas por recursos e, consequentemente, prejudicam seu pleno desenvolvimento, são responsáveis por perdas significativas no setor agrícola, ano após ano. Portanto, conhecer o status sanitário da lavoura é um fator crucial no planejamento de ações de manejo, além de embasar políticas públicas de investimento e de proteção, a serem adotadas, com o objetivo de prevenir perdas produtivas e de assegurar a segurança … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Most phytosanitary problems trigger plant defense mechanisms, changing and/ or reducing vegetative growth, and hence decreasing biomass, leaf area index, or other canopy parameters. Accordingly, detection of canopy changes by active sensors can reveal the occurrence of plant-health problems such as pest infestation (Barros et al, 2021).…”
Section: Remote Sensingmentioning
confidence: 99%
“…Most phytosanitary problems trigger plant defense mechanisms, changing and/ or reducing vegetative growth, and hence decreasing biomass, leaf area index, or other canopy parameters. Accordingly, detection of canopy changes by active sensors can reveal the occurrence of plant-health problems such as pest infestation (Barros et al, 2021).…”
Section: Remote Sensingmentioning
confidence: 99%
“…An important point to be highlighted in optical sensor data processing is the use of different vegetation indices, with the Normalized Difference Vegetation Index (NDVI) being one of the best known and used. There are structural and biochemical indices; in Barros et al (2021), a brief list of some of these indices can be found, as well as in Bagheri (2020).…”
Section: Remote Sensingmentioning
confidence: 99%
“…Some active sensors record bands in the visible spectrum (Light Detection and Ranging -LIDAR) or the microwave spectrum (Radio Detecting and Ranging -RADAR). More details about the different sensor types used in Remote Sensing can be found inBarros et al (2021).Studies on the relationship of Low Altitude Aerophotogrammetry and ProximalRemote Sensing with Agricultural Entomology have increased significantly in recent years.…”
mentioning
confidence: 99%